Quality assessment on storage of sweetened nata de coco produced by the Salvacion Small Coconut Farmers and Producers Association (SSCFPA) in Buenavista, Guimaras - Inderio, Belen Paderog
Sweetened nata de coco produced by the Salvacion Small Coconut Famrers and Producers Association (SSCFPA) in Buenavista, Guimaras was assessed in terms of its quality.